EKSISTENSI PERADILAN KONEKSITAS DALAM PERKARA TINDAK PIDANA KORUPSI DI INDONESIA PASCA LAHIRNYA KOMISI PEMBERANTASAN KORUPSI - Faldi Ahmad Jurio; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Corruption can be committed by any community. Did not rule out the possibility of being carried out by members of the military (TNI) together with civilians, who formally must be tried legally in court koneksitas. Connection cases both for general crime and special crime (corruption). The legal basis of justice trials is regulated in Article 89 of the Criminal Procedure Code, Article 198 of Law Number 31 of 1997 concerning Military Justice and Article 16 of Law Number 48 of 2009 concerning Judicial Power. And with the enactment of Law Number Law Number 48 of 2009 concerning Judicial Power, an implementation regulation regarding Article 16 is needed, so that there is uniformity in the provisions of the Articles concerning justice trials.The purpose of this thesis is: First, to find out how the existence of koneksitas justice in corruption cases in Indonesia after the birth of the Corruption Eradication Commission. Second, to find out the strengths and weaknesses of koneksitas justice in prosecuting corruption cases in Indonesia after the birth of the Corruption Eradication Commission.This type of research is normative legal research or can also be called doctrinal legal research. From the results of the study, based on two problem formulations can be concluded. First, the existence of the koneksitas justice in corruption cases after the birth of the corruption eradication commission should be paid more attention. Considering that justice is already regulated in the Criminal Procedure Code and Law Code. The legal culture that occurs should also be fairer and don't look at the feather in handling the law. Law enforcement officials must also be more assertive in handling corruption cases between two courts. in order to create legal certainty. Second, the strengths and weaknesses in connection justice should be a reference for using that trial. Because justice connectivity is designed to facilitate coordination and resolution of corruption cases between the two courts. The criminal process if using connectivity will also be more fair and transparent because it is tried in one court. Connectivity justice also benefits both parties because they remember that members of the military have their own judiciary in handling corrupt acts committed by members of the TNI.Key words: Military-Corruption Justice-Military-Corruption-Corruption Eradication Commiss